2005
DOI: 10.1021/ma047642h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclic Polymers:  Ring-Expansion Reaction of Cyclic S-Dithioester with Thiiranes

Abstract: The ring-expansion reaction of equimolar cyclic dithioester 1 with 3-phenoxypropyrene sulfide (PPS) (cyclic dithioester 1/PPS ) 1/2) was examined in the presence of TBAC as a catalyst in NMP for 24 h. It was found that intermolecular ester-exchange reaction occurred during the insertion reaction of PPS into cyclic dithioesters, and cyclic polymers with M ns ) 3600-8900 were obtained in 80-96% yields. The structures of the obtained cyclic polymers were confirmed by the 1 H NMR, 13 C NMR IR, and MALDI TOF-MS spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 13 publications
0
44
0
3
Order By: Relevance
“…Two reactive thermolabile SAC bonds in a cyclic aromatic bis(dithioester) were the structural prerequisites enabling the insertion of thiiranes (Scheme 60). 248 However, high molar masses were not obtained by this method.…”
Section: Reps Of Various Monomersmentioning
confidence: 91%
See 2 more Smart Citations
“…Two reactive thermolabile SAC bonds in a cyclic aromatic bis(dithioester) were the structural prerequisites enabling the insertion of thiiranes (Scheme 60). 248 However, high molar masses were not obtained by this method.…”
Section: Reps Of Various Monomersmentioning
confidence: 91%
“…[244][245][246][247][248] They are based on four different classes of cyclic initiators, four different classes of monomers, and four different reaction mechanisms.…”
Section: Reps Of Various Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…When the insertion reaction of PPS into CD (CD/PPS = 1/50) was carried out using TBAC catalyst, the corresponding large cyclic polysulfide with M n ¼ 42000, M w =M n ¼ 4:50 was obtained (Scheme 14). 53 This is a unique reaction system for the synthesis of cyclic polymers; the size of the cyclic polymers increased with the polymerization as it proceeded. It was also found that an intermolecular ester-exchange reaction occurred as an unexpected reaction during the insertion reaction of PPS into CD.…”
Section: Synthesis Of Polymers With Complex Architecturesmentioning
confidence: 99%
“…It was also found that an intermolecular ester-exchange reaction occurred as an unexpected reaction during the insertion reaction of PPS into CD. 53 …”
Section: Synthesis Of Polymers With Complex Architecturesmentioning
confidence: 99%